Efektivitas model project-based learning pada pembelajaran IPA terhadap literasi sains: Systematic literature review - Velita Nuraini; Sri Wahyuni; Sri Rejeki Dwi Astuti; Siti Shofa Assyifaul Qulbi Barid (Papanda Journal of Mathematics and Science Research, 2026)
The 21st century demands individuals to possess adequate scientific literacy to navigate technological advancements and global challenges. Scientific literacy entails understanding scientific concepts and strengthening abilities critical thinking. However, the 2022 PISA results revealed that Indonesian learners’ scientific literacy remains low, with a mean score of 383, below the OECD average. This condition calls for the implementation of effective learning models, among them is Project Based Learning (PjBL). This research seeks to examine the application of PjBL in science learning and how it affects students’ scientific literacy through a Systematic Literature Review (SLR). Fifteen articles obtained from Google Scholar were analyzed using the keywords “Model Project Based Learning” “Literasi Sains” “Siswa Sekolah” and “Pembalajaran IPA” with the selection process following PRISMA guidelines. The analysis shows that PjBL positively influences the improvement of scientific literacy across educational levels. At the elementary level, PjBL helps students grasp scientific concepts through contextual project activities. In lower secondary school, the integration of digital media such as E-LKPD and liveworksheets enhances students’ scientific reasoning. In upper secondary school, the combination of PjBL with STEM approaches and cultural contexts effectively strengthens higher-order thinking skills. Overall, PjBL is proven to be a relevant model for improving students’ scientific literacy by promoting active, collaborative, and project-oriented learning which fosters the growth of 21st-century skills.